(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The most modern buildings of the Middle Ages were built in the cities of Samarkand and Shahrisabz during the era of Amir Temur and the Timurids, when they were the capital of the world culture of Central Asia. Among these buildings, one of the masterpieces of Amir Temur’s reign, the Aksaroy Palace, built in his birthplace, is particularly important. The article presents scientific information about the construction history of the Oksaroy architectural monument and its role in world civilization. Also, scientific hypotheses about the construction process of the Aksaroy building and its initial appearance were put forward.